Elevated neutrophil extracellular traps by HBV‐mediated S100A9‐TLR4/RAGE‐ROS cascade facilitate the growth and metastasis of hepatocellular carcinoma. Issue 2 (8th November 2022) - Zhan, Xi; Wu, Rui; Kong, Xue‐Hua; You, Yan; He, Kun; Sun, Xiao‐Yu; Huang, Yong; Chen, Wei‐Xian; Duan, Liang
Abstract: Background: Neutrophil extracellular traps (NETs) are considered significant contributors to cancer progression, especially metastasis. However, it is still unclear whether NETs are involved in hepatitis B virus (HBV)‐related hepatocarcinogenesis and have potential clinical significance during evaluation and management for hepatocellular carcinoma (HCC). In this study, we aimed to investigate the functional mechanism of NETs in HBV‐related hepatocarcinogenesis and their clinical significance. Methods: A total of 175 HCC patients with and without HBV infection and 58 healthy controls were enrolled in this study. NETs were measured in tissue specimens, freshly isolated neutrophils and blood serum from these patients, and the correlation of circulating serum NETs levels with malignancy was evaluated. The mechanism by which HBV modulates NETs formation was explored using cell‐based studies. In addition, in vitro and in vivo experiments were further performed to clarify the functional mechanism of NETs on the growth and metastasis of HCC. Results: We observed an elevated level of NETs in blood serum and tissue specimens from HCC patients, especially those infected with HBV. NETs facilitated the growth and metastasis of HCC both in vitro and in vivo, which were mainly dominated by increased angiogenesis, epithelial‐mesenchymal transition (EMT)‐related cell migration, matrix metalloproteinases (MMPs)‐induced extracellular matrix (ECM) degradation and NETs‐mediated cell trapping. Inhibition of NETs generation by DNase 1 effectively abrogated the NETs‐aroused HCC growth and metastasis. In addition, HBV‐induced S100A9 accelerated the generation of NETs, which was mediated by activation of toll‐like receptor (TLR4)/receptor for advanced glycation end products (RAGE)‐reactive oxygen species (ROS) signaling. Further, circulatory NETs were found to correlate with viral load, TNM stage and metastasis status in HBV‐related HCC, and the identified NETs could predict extrahepatic metastasis, with an area under the ROC curve (AUC) of 0.83 and 90.3% sensitivity and 62.8% specificity at a cutoff value of 0.32. Conclusions: Our findings indicated that activation of RAGE/TLR4‐ROS signaling by HBV‐induced S100A9 resulted in abundant NETs formation, which subsequently facilitated the growth and metastasis of HCC cells. More importantly, the identified circulatory NETs exhibited potential as an alternative biomarker for predicting extrahepatic metastasis in HBV‐related HCC.